2001
DOI: 10.1073/pnas.171310198
|View full text |Cite
|
Sign up to set email alerts
|

How cuckoldry can decrease the opportunity for sexual selection: Data and theory from a genetic parentage analysis of the sand goby, Pomatoschistus minutus

Abstract: Alternative mating strategies are common in nature and are generally thought to increase the intensity of sexual selection. However, cuckoldry can theoretically decrease the opportunity for sexual selection, particularly in highly polygamous species. We address here the influence of sneaking (fertilization thievery) on the opportunity for sexual selection in the sand goby Pomatoschistus minutus, a marine fish species in which males build and defend nests. Our microsatellite-based analysis of the mating system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
146
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(154 citation statements)
references
References 43 publications
4
146
0
1
Order By: Relevance
“…The Pmin20 locus was excluded from the analysis because, after genotyping more than 90 individuals, the number of alleles almost matched the number of fish genotyped. The studies of Jones et al (2001) and Pampoulie et al (2004) also observed microsatellite markers with a very high number of alleles. By organizing a better sampling strategy and using straightforward N e -estimation methods incorporating migration (Wang and Whitlock, 2003), better estimates of the N e might confirm the expected high N e for P. minutus.…”
Section: Discussionmentioning
confidence: 95%
“…The Pmin20 locus was excluded from the analysis because, after genotyping more than 90 individuals, the number of alleles almost matched the number of fish genotyped. The studies of Jones et al (2001) and Pampoulie et al (2004) also observed microsatellite markers with a very high number of alleles. By organizing a better sampling strategy and using straightforward N e -estimation methods incorporating migration (Wang and Whitlock, 2003), better estimates of the N e might confirm the expected high N e for P. minutus.…”
Section: Discussionmentioning
confidence: 95%
“…Extrapair components of fitness may increase or decrease the standardized variance in male reproductive success (I s ), depending on how within-pair and extrapair fertilization success covary (Webster et. al 1995;Jones et al 2001). If the covariance is minimal or negative, EPP may have little effect on the opportunity for sexual selection.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, if many extrapair young are sired by floaters not included in the sample (Kempenaers et al 2001), the study will fail to reveal a negative covariance between within-pair and extrapair success among true breeders since, by definition, floaters sire no within-pair offspring. I s will thus be overestimated while variation in apparent success (I s,app ) will be underestimated, making EPP seem much more influential than it truly is in generating variance in reproductive success among males (Jones et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is followed up by a contribution in which Shuster et al [14] develop a quantitative framework to measure the impact that polyandry has on the variance in reproductive success, and thus on the opportunity of sexual selection in a population. The approach proposed helps contextualize recent empirical demonstrations of the strong impact that polyandry can have on different episodes of sexual selection [15,16]. Another fundamental consequence of polyandry is that the operation of pre-and post-copulatory episodes of selection favours the evolution of alternative mating tactics.…”
Section: Scopementioning
confidence: 99%